PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIVISI OFFICE BOY (OB) PADA KEMENKO MARVES JAKARTA PUSAT - Muhammad Jihad Akbar; Andi Sopandi (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of motivation and work discipline on employee performance at the Coordinating Ministry for Marves, Central Jakarta, both partially and simultaneously. The method used was quantitative by collecting data through questionnaires filled in by 59 respondents, with a population of 59 people and a sample of 59 people. Data analysis techniques include simple linear regression tests, multiple linear regression, correlation coefficients, coefficients of determination, as well as t tests and f tests. The research results show that motivation has a significant effect on employee performance, with a regression equation Y = 22.737 + 0.512X1, a correlation value of 0.556 (medium), and a coefficient of determination of 29.7%. The t test shows the t-count of 4.053 which is greater than the t-table of 2,002 with a significance value of 0.000 < 0.05. Work discipline also has a significant effect on employee performance, with a regression equation of Y = 9.339 + 0.803X2, a correlation value of 0.806 (very strong), and a coefficient of determination of 64.4%. The t test for work discipline produces a t-count of 10.291, which is greater than the t-table of 2,002 with a significance value of 0.000 < 0.05. Simultaneously, Work Motivation and Discipline have a significant effect on Employee Performance, with a regression equation Y = 8.248 + 0.093X1 + 0.741X2, a correlation value of 0.807 (very strong), and a coefficient of determination of 64.4%. The results of the f test show that the F-count is 53.551 which is greater than the F-table of 3.16 with a significance value of 0.000 < 0.05.